Upgrading of Milner and Klipfontein Road Southbound Approach to alleviate traffic issues - Barnes, Faragh (Department of Civil Engineering, 2021)
Introduction The population of the world is increasing at a rate of 1.07% each year. In order to accommodate this growth, quality and efficiency of services need to be improved. This includes improving the quality and efficiency of the transportation services, as a country's sustainability is reliant upon these systems. In many countries, the increase in population has congested the CBD areas, forcing people to migrate outside of the CBD. This has resulted in urban sprawl. However, the apartheid era has resulted in urban sprawl in South Africa, which left many people living along the periphery, close to the industrial areas and a distance away from the CBD. One of the biggest challenges people living outside of the CBD area experience, is a poor and unreliable public transport system. It is difficult for people to access other areas and this has increased the number of private vehicles on the road. According to a list of the top 10 countries with the highest public transport ridership, that was developed by Worldatlas.com (2019), Kenya has the highest public transport ridership. Of the total population, 63% of the people use public transport. Furthermore, the other 9 countries mentioned have ridership volumes ranging from 53% to 57%. This proves that 40% to 50% of the population in other countries is still using private vehicles above public transport and this is still considered high. Research Problem The use of private vehicles in South Africa has been on the rise. As a result, the congestion levels on the roads have increased. This has resulted in longer travel times, busier roads and an increase in road accidents as drivers spend more time travelling to and from destinations. Milner and Klipfontein Road is located in Mowbray. The intersection is surrounded by a shopping mall, a hospital, a clinic, a school and a number of other amenities. Therefore, the traffic travelling through this intersection daily is relatively high. The southbound approach of Milner and Klipfontein Road intersection, however, has the highest volume of traffic operating through the intersection daily, as it connects the M5 highway (Class 2) and Raapenberg Road (Class 3) to Klipfontein Road (Class 3). The southbound approach is a three-lane approach, of which one lane is a short turning lane. With high volumes of traffic operating through this approach daily, the road tends to get very congested, especially during the peak period. The high congestion levels have resulted in a number of other issues, which include longer travel times from Alexandra and Raapenberg Road intersection to Milner and Klipfontein Road intersection, vehicles struggling to change lanes due to limited gap length available and spilling of traffic onto Raapenberg Road. This study will, therefore, focus on finding suitable measures to assist with alleviating the congestion as well the other issues currently being experienced along the southbound approach of Milner and Klipfontein Road. Literature Review It is important to manage the transport system as this affects the economy of the country. There are two types of traffic congestion and they are either recurrent or non-recurrent. Traffic congestion is a result of having too many vehicles on the road i.e. when the demand is larger than the supply. It is, therefore, necessary to improve the quality of a road or an intersection. There are three types of intersection designs and they include: priority control, traffic signals and rotary movement control. It is important to determine the most efficient way for an intersection to operate by determining the way in which conflicting volumes will be served. To avoid undesirable delays and deal with large volumes of traffic, signalised or rotary movement is often preferred. At signalised intersections, it is important to measure the effectiveness of an intersection by evaluating its performance and the design of the signal process as this can affect the time of travel, choice of route, mode of transport and If the route will be completed. To measure the effectiveness of the signalised intersection, the following elements must be assessed: the capacity, the volume to capacity ratio, the delay and the queue length. The Level of Service (LOS) also plays an important role in determining the operation of the intersection and provides the engineer or designer with information related to the type of flow or movement at each approach and intersection. The signal design plays an important role in the operation of the intersection too. It is important to ensure that the signal timing is correct as this can affect the flow of traffic. There are different signal controls that can be implemented, and they include, semi actuated, fully actuated and fixed timing. To retime a signalised intersection is considered the most cost-effective method of redesign. Phasing of the intersection is important as this can affect the level of service of operation of the intersection. To determine which phasing is necessary, the following must be assessed: the number of road accidents, the sight distance available, the geometry of the road, speeds of vehicles, the total volumes and the operation of the intersection. Unsignalised intersections are generally not preferred as volumes and speeds differ at each approach. High accident statistics are expected. This affects the overall capacity and operation of an intersection. Rotary movement control which refers to roundabouts or traffic circles, can handle larger volumes of traffic and reduce conflicting movements. They are therefore, considered much safer than other forms of at-grade intersections. The literature review will provide more detail regarding traffic congestion, intersection design and measuring the effectiveness of an intersection. Data collection and Analysis The site investigation was undertaken on 20 February 2019 between the AM peak (6:00 and 8:30) and the PM peak (16:00 and 18:30), to determine the extent of the traffic congestion currently being experienced, along the southbound approach of Milner and Klipfontein Road. Based on the findings, the PM peak period was considered the “worst case scenario”. A traffic count was not required; as previous traffic count data was available from the City of Cape Town records. A full traffic count was completed in 2017 for the entire intersection. A travel time survey was undertaken on Wednesday, 24 July 2019 between 16:00 and 18:00. The runs were calculated at 10-minute intervals. The data obtained from this survey was validated against the traffic count survey to determine whether the data obtained from City of Cape Town records, was indeed correct. It should be noted that the travel time survey was only completed during the PM peak, as the majority of traffic travel along that approach (direction towards home), during the PM peak. It was also confirmed to be the time of day when traffic was the worst. During the process of the travel time survey, a separate survey was completed to determine the direction in which vehicles were travelling. The vehicles were monitored from where they entered the southbound approach (M5 highway or Raapenberg Road), whether they stayed in the lane they entered the approach or whether they changed lanes. This survey would determine the destination of travel. Furthermore, vehicles changing lanes, were also further monitored, to determine if they were undertaking this movement legally or illegally. A solid white line, located approximately 200m away from the signalized Milner and Klipfontein intersection, separates the two lanes entering from M5 highway and Raapenberg Road. It prevents vehicles from changing lanes when unsafe to do so. The data was captured in Sidra and Junction to assess the delay and level of service at the intersection and specifically along the southbound approach of Milner and Klipfontein Road intersection. Results and findings The southbound approach is a three-lane approach. It comprises of a left lane, which is used for straight ahead movements and left turning movements, a middle lane used for straight ahead movements and a short right turn lane. The traffic count data that was obtained from the City of Cape Town records for 2017, established that a high volume of traffic passed through Milner and Klipfontein Road intersection daily. The peak periods of the day had a variation in the volumes of traffic along each approach, except for the southbound approach, which had high volumes of traffic at both peak periods. Majority of the traffic enters from either M5 highway or Raapenberg Road and exits onto Milner or Klipfontein Road eastbound. The signal phasing at the intersection comprises 4 phases, with no priority given to the southbound approach eastbound movements, even though the highest traffic volumes travelling in that direction. This has resulted in traffic congestion and a backlog of traffic onto Raapenberg Road. As a result, vehicles take longer than necessary to reach the intersection. The travel time survey investigated vehicles travelling from Alexandra and Raapenberg Road towards Milner and Klipfontein Road. The total distance is 1.2km in length. On average, a driver driving at a speed of 60km/hr. (length of road is short, and it bends), should take 3 minutes and 20 seconds to complete this stretch of road. This total time is inclusive of the signal system. It took vehicles more than 7 minutes to complete the 1.2km distance. The road accident statistics also indicate that a high number of accidents take place at Milner and Klipfontein Road intersection. Over the latest five-year period, a total of 256 accidents took place at the intersection. Of the 256 accidents, 53% of the accidents took place along the southbound approach. Furthermore, the directional survey also established that majority of the vehicles entering from both Raapenberg and the M5 highway, were travelling eastbound along Klipfontein Road. Majority of the vehicles changing lanes, have however, done this legally (not crossing the solid line). As a result, many vehicles were merged between two lanes, obstructing oncoming vehicles. It is evident from the results that there is a need for mitigating measures. High volumes of traffic are experienced along the southbound approach, with a high portion of this traffic wanting to make use of the left lane. Limited gaps are available for changing lanes, travel time is longer than expected and spilling of traffic is occurring on Raapenberg Road all due to high congestion levels along the southbound approach. It is therefore proposed that a roundabout be constructed at Milner and Klipfontein Road intersection to reduce conflicting movements, improve the delay and LOS of the intersection and reduce the issues currently being experienced along the southbound approach. Recommendations It is recommended that a proper design be completed to understand the proper effects in terms of operation of the intersection by implementation of a roundabout. Further research should be undertaken to determine the effect of the roundabout on the AM peak.